From Telecourses to Online Courses: A Story of Redesign | Du cours télévisé au cours en ligne : une histoire de redesign - Potvin, Claude (Canadian Journal of Learning and Technology, 2015)
This case deals with the redesign of a standard telecourse - printed material, professional studio video recordings and phone tutoring – into an online course. The redesign involved an adjunct professor in the Humanities having some experience in distance education but little with learning technologies. It was a two-year project including the grant application process. The main issues included replacing television-based content with multimedia content; understanding the complexity of interactions between materials, students, and tutors; and adapting traditional assessment approaches to online instruments and methods.